PENGARUH DISIPLIN KERJA DAN REWARD TERHADAP KINERJA KARYAWAN PT JASA ANGKASA SEMESTA JAKARTA - Rini Saraswati Dewan; Muhammad Yuda Alhabsyi (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of work discipline and rewards on employee performance with the object of this research company is PT Jasa Angkasa Semesta. The method used in this study is a quantitative method, primary data collection techniques and secondary data, the sample that sample is saturated with the number of population and samples of 63 employees through research techniques (questionnaires of 63 respondents or employees), observation, literature study. The analysis method used in this study is the validity test, reliability test, classical assumption test, simple and multiple linear regression test, correlation coefficient test, determination test and significance test (t test and F test). The results of the work discipline correlation coefficient are 0.670 or 67.0% and the reward correlation coefficient value is 0.666 or 66.6%. So it can be interpreted that the relationship between work discipline and reward variables on employee performance is a strong correlation. The determination coefficient value is obtained at 44.9%. While the remaining 55.1% is influenced by other factors. It is known that the significant value for the influence of work discipline on employee performance is 0.000 <0.05 and the calculated t value is 3.574> t table 1.999, it can be concluded that Ho is rejected and Ha is accepted, which means that there is an influence of work discipline on employee performance. It is known that the significant value for the influence of rewards on employee performance is 0.000 <0.05 and the calculated t value is 3.468> t table 1.999, it can be concluded that Ho is rejected and Ha is accepted, which means that there is an influence of rewards on employee performance. And it is known that the significant value for the influence of work discipline and rewards on employee performance is 0.000 <0.05 and the calculated f value is 35.326> F table 3.15, it can be concluded that Ho is rejected and Ha is accepted, which means that there is an influence of work discipline and rewards on employee performance at PT Jasa Angkasa Semesta.